Genetic Diversity Of Duabanga Moluccana Using Dominant Dna Markers Based On Inter-Simple Sequence Repeats In Sarawak - Ho Wei, Seng; Diyanah, M.J; Liew, K.S.; Pang Shek, Ling; Ismail, Jusoh; Julaihi, Abdullah (2012)
Duabanga moluccana or locally known as Sawih is a widely known forest tree species for its multipurpose timber and other natural products such as fibers. Genetic diversity investigation of this species can provide baseline information for indirect selection in tree improvement programme. This study has employed Inter Simple Sequence Repeat (ISSR) technique to assess the genetic diversity and relatedness within and between three populations of D. moluccana located in Sarawak, namely, Mukah, Tatau (Bintulu) and Niah. A total of 151 loci from 90 individuals were successfully amplified with 6 selected ISSR primers and the percentage of polymorphic loci was 90.1%. The Shannon’s diversity index showed that D. moluccana in Mukah natural forest (0.429) was the most diverse compared to Tatau (Bintulu) (0.362) and Niah natural forest (0.387). Neighbour joining tree were constructed to show relationship among the selected populations. The overall populations were completely clustered into three main groups, according to their corresponding population. Based on these results, it implies that D. moluccana trees are genetically diverse among populations.